The Industrialization of Depressed Areas in Italy: Data and Commentary - Bozzola, G.B. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1961)
SummaryThe Author casts some light upon the factors influencing the industrialization of Southern Italy, the economic and political problems raised by the phenomenon, and their consequences.